High Carbon Steel Plate
Patent Information
- Application Number
- JP2021010251
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-28
- Filing Date
- 2021-01-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-01-26
AI Technical Summary
【0017】 本発明によれば、焼入れ前の加熱温度を高くしても良好な硬さと靭性のバランスを安定的に有する鋼板部材を製造できる高炭素鋼板を提供することができる。
Smart Images

Figure 0007631008000001 
Figure 0007631008000002 
Figure 0007631008000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a high carbon steel sheet, and in particular to a high carbon steel sheet useful as a processing material for cutlery, springs, power springs, tools, and the like. [Background technology]
[0002] High carbon steel sheets are widely used as processed materials for automobile drive system parts such as chains, gears, and clutches, blades, springs, tools, etc. When producing such steel sheet members from high carbon steel sheets, the high carbon steel sheets are usually punched and shaped, and then subjected to heat treatment such as quenching and tempering to obtain a desired hardness.
[0003] Among these, steel plate members such as various blades such as circular saws, band saws, and carters, springs, springs, and tools require not only hardness but also good toughness so that the cutting edge does not break during use. Usually, when manufacturing such steel plate members from high carbon steel plate, a good balance between hardness and toughness is obtained by avoiding high temperature or long time heating during heat treatment after forming, especially before quenching. Specifically, by avoiding high temperature heating, excessive dissolution of undissolved carbide in the microstructure of the steel plate member is suppressed, thereby preventing coarsening of austenite grains, and as a result, good toughness is obtained.
[0004] For example, Patent Document 1 describes a steel sheet having a chemical composition, in mass %, of C: 0.4-0.75%, Si: 0.5 or less, Mn: 0.5-2%, P: 0.02% or less, S: 0.02% or less, Ti: 0-0.2%, V: 0-0.5%, and Nb: 0-0.5%, and containing at least one of V, Ti, and Nb: 0.02-0.5%, Ti: 0.02-0.2%, and Nb: 0.01-0.5%, with the balance being Fe and unavoidable impurities, in which the X value defined by the following formula (1) is 10 or less, the prior austenite grain size is 15 μm or less, and the amount of undissolved carbides having a circle equivalent diameter of 1.5 μm or more is 0.1 mm 2 The publication describes a steel material for cutlery having excellent wear resistance and toughness and a tempered martensite structure with 40 or less particles per square inch. X = 15.3 × {C - 0.25(V + Ti) - 0.13Nb} - [area ratio of undissolved carbide (%)] (1)
[0005] Patent Document 1 also describes that for the hardening treatment in this manufacturing method of steel for blades, suitable hardening treatment conditions can be found within the range of a liquidus heating holding temperature of 790 to 900°C and a holding time of 10 to 60 minutes, and that if the heating holding temperature exceeds 900°C or the heating holding time exceeds 60 minutes, the prior austenite grain size is likely to become coarse, making it difficult to stably obtain high toughness. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2009-161809 A Summary of the Invention [Problem to be solved by the invention]
[0007] As described above, in the manufacture of steel plate members such as blades, the heating temperature before quenching is usually set to a temperature not exceeding 900°C, generally 800°C to 850°C, to obtain not only the desired hardness but also good toughness.
[0008] On the other hand, there are cases where the heating temperature before quenching is required to be higher than 850°C, particularly higher than 900°C, for various reasons.
[0009] For example, depending on the heat treatment equipment, it may be difficult to quickly perform quenching after removing the steel plate member from the heating furnace due to reasons such as the long distance from the heating furnace to the quenching device. In such cases, the quenchability becomes unstable, but the quenchability can be stabilized by increasing the heating temperature before quenching in advance. Alternatively, if temperature unevenness occurs in the heating furnace, the austenitization of the steel plate member may become partially insufficient, resulting in unstable quenchability. Against this problem, the occurrence of temperature unevenness can be prevented by increasing the heating temperature before quenching in advance.
[0010] However, if the heating temperature before quenching is increased, the hardness stability of the steel plate member is improved, but as described above, the austenite grains in the microstructure of the steel plate member become coarse, resulting in a decrease in toughness. Therefore, a processed material is required that can impart good hardness to the steel plate member manufactured after quenching and tempering without causing a decrease in toughness even when the heating temperature before quenching is increased.
[0011] Therefore, an object of the present invention is to provide a high carbon steel plate from which a steel plate member can be manufactured that stably has a good balance between hardness and toughness even when the heating temperature before quenching is increased. [Means for solving the problem]
[0012] The present inventors have conducted extensive research to solve the above problems and have arrived at the present invention. That is, the present invention includes the following preferred embodiments.
[0013] The high carbon steel sheet according to the present invention has C: 0.75% by mass or more and 1.10% by mass or less, Si: 0.05% by mass or more and 0.40% by mass or less, Mn: 0.05% by mass or more and 0.70% by mass or less, Cr: 0.35% by mass or less, Nb: 0.005 mass% or more and 0.030 mass% or less, Ti: 0.02% by mass or less, Al: 0.001 mass% or more and 0.050 mass% or less, P: 0.03% by mass or less, and S: 0.01% by mass or less and the balance being Fe and unavoidable impurities, The microstructure of the steel sheet consists of ferrite and cementite.
[0014] In the above-mentioned high carbon steel plate, the spheroidization rate of the cementite is preferably 70% or more.
[0015] In the above-mentioned high carbon steel sheet, in the microstructure of the steel sheet, 2 It is more preferable that the number of cementite grains per unit area is 200 or more.
[0016] In addition, the high carbon steel plate mentioned above has the following features: Mo: more than 0% by mass and 0.5% by mass or less, B: More than 0% by mass and 0.005% by mass or less, Ni: more than 0 mass% and 0.5 mass% or less, and V: More than 0% by mass and 0.35% by mass or less It is more preferable that the composition has one or more components selected from the group consisting of: Effect of the Invention
[0017] According to the present invention, it is possible to provide a high carbon steel plate from which a steel plate member having a good balance between hardness and toughness can be produced stably even if the heating temperature before quenching is increased. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The inventors conducted extensive research into high carbon steel plates that can be used to manufacture steel plate members that have a stable balance between hardness and toughness even when the heating temperature before quenching is high, and focused on their component composition to complete the present invention.
[0019] In this specification, "hardness" refers to hardness based on Vickers hardness (HV), except where Rockwell hardness (HRB) is specified. Vickers hardness can be determined by a method described in detail in the Examples below. Furthermore, in this specification, "toughness" refers to bendability based on a bending angle (°) calculated from a VDA bending test. The bending angle calculated from a VDA bending test can be determined by a method described in detail in the Examples below.
[0020] Specifically, it was found that by controlling the content of Nb in the composition of the high carbon steel plate to be within a specific range and controlling the content of Ti to be equal to or less than a specific content, the deterioration of the toughness of the steel plate member manufactured after heat treatment can be suppressed even if the heating temperature before quenching is increased. This is because NbC, a carbide of Nb, is stable even at high temperatures without dissolving, and even if the microstructure of the steel plate member after heat treatment does not contain undissolved carbides, the dispersed NbC can keep the austenite grains fine. On the other hand, TiC, a carbide of Ti, generates coarse inclusions TiN that become the starting point of cracks, so the content must be controlled. Furthermore, when the austenite grains are kept fine by including undissolved carbides in the steel plate member as in the conventional technology, the undissolved carbides can also become the starting point of cracks during bending deformation, resulting in a decrease in the bendability of the steel plate member. In the present invention, NbC contained in the steel plate member is dispersed extremely finely to refine the austenite grains, so that the bendability of the steel plate member can be improved.
[0021] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.
[0022] 1. Ingredient composition The high carbon steel sheet in this embodiment has the following main component composition.
[0023] [C: 0.75 mass% or more and 1.10 mass% or less] C is an element necessary for improving the hardness of steel plate and steel plate members after heat treatment. Therefore, the C content is 0.75 mass% or more. Furthermore, the C content is preferably more than 0.75 mass%, more preferably 0.80 mass% or more, even more preferably 0.82 mass% or more, and even more preferably 0.84 mass% or more. On the other hand, if the C content is too high, the amount of coarse undissolved carbides that adversely affect toughness and impact properties increases. Therefore, the C content is 1.10 mass% or less, preferably 1.07 mass% or less, and more preferably 1.04 mass% or less.
[0024] [Si: 0.05 mass% or more and 0.40 mass% or less] Si is an element that acts as a deoxidizer for steel. In order to effectively exert this function, the Si content must be 0.05 mass% or more. The Si content is preferably 0.10 mass% or more, more preferably 0.20 mass% or more. On the other hand, if the Si content is too high, the workability, particularly the bendability, of the steel plate and the steel plate member after heat treatment may decrease. Therefore, the Si content is 0.40 mass% or less, preferably 0.30 mass% or less, more preferably 0.25 mass% or less.
[0025] [Mn: 0.05 mass% or more and 0.70 mass% or less] Mn has the effect of improving the hardenability of steel. In order to effectively exert such an effect, the Mn content must be 0.05 mass% or more. The Mn content is preferably 0.10 mass% or more, more preferably 0.20 mass% or more. On the other hand, if the Mn content is excessive, the martensite transformation point Ms decreases, the heat treatment distortion increases, and the toughness and productivity decrease. Therefore, the Mn content is 0.70 mass% or less, preferably 0.50 mass% or less, more preferably 0.45 mass% or less, and further preferably 0.40 mass% or less.
[0026] [Cr: 0.35% by mass or less] Cr has the effect of improving the hardenability of steel, and by including a certain amount of Cr, it can promote the formation of coarse spheroidized carbides during annealing, making the steel softer. In order to effectively exert such an effect, the Cr content is preferably more than 0 mass%, more preferably 0.01 mass% or more, even more preferably 0.05 mass% or more, and even more preferably 0.10 mass% or more. On the other hand, if Cr is excessive, the toughness may deteriorate. Therefore, the Cr content is 0.35 mass% or less, preferably 0.30 mass% or less, and more preferably 0.25 mass% or less.
[0027] [Nb: 0.005 mass% or more and 0.030 mass% or less] Nb produces carbides such as NbC. Unlike cementite, NbC does not melt and remains stable even at high temperatures of 900°C or higher, and can prevent the movement of austenite grain boundaries at the high temperatures to suppress the coarsening of austenite grains. For this reason, the Nb content must be 0.005% by mass or more. The Nb content is preferably 0.01% by mass or more, more preferably 0.015% by mass or more. In order to achieve such an effect, it is necessary to melt NbC once during slab heating before hot rolling, and to precipitate it finely again at the coiling stage after hot rolling. On the other hand, if a large amount of Nb is added to the high carbon steel sheet in this embodiment having a high C content, it becomes difficult to melt NbC during the heating. Therefore, the Nb content is 0.030% by mass or less, preferably 0.025% by mass or less, and more preferably less than 0.020% by mass.
[0028] [Ti: 0.02% by mass or less] Ti, like Nb, produces TiC, a carbide, and remains stable even at high temperatures without dissolving. It has the effect of preventing the movement of austenite grain boundaries and suppressing the coarsening of austenite grains. However, the coarse inclusions TiN inevitably produced by the addition of Ti become the starting point of cracks, lowering the toughness of the steel plate and the steel plate member after heat treatment. Therefore, the Ti content must be 0.02 mass% or less. The Ti content is preferably less than 0.02 mass%, more preferably 0.015 mass% or less, and even more preferably 0.01 mass% or less. Alternatively, the Ti content may be 0 mass%. That is, the Ti content may be in the range of 0 mass% or more and 0.020 mass% or less.
[0029] [Al(sol-AL): 0.001 mass% or more and 0.050 mass% or less] Al acts as a deoxidizer for steel, and fixes the solute N present in steel as AlN, improving the cold workability of the steel sheet. In order to effectively exert such an effect, the Al content must be 0.001% by mass or more. However, if the Al content is excessive, Al2O3, which becomes an inclusion, is excessively generated in the steel sheet, which may deteriorate the cold workability. Therefore, the Al content is 0.050% by mass or less. The Al content is preferably 0.04% by mass or less, more preferably 0.01% by mass or less, and even more preferably 0.008% by mass or less.
[0030] [P: 0.03 mass% or less] P is inevitably present as an impurity element, and segregates at grain boundaries to deteriorate the bendability of steel sheets and steel sheet members. Therefore, the P content must be 0.03 mass% or less. The P content is preferably 0.02 mass% or less, more preferably 0.015 mass% or less, and further preferably 0.010 mass% or less. Alternatively, the P content may be 0 mass%. In other words, the P content may be in the range of 0 mass% or more and 0.03 mass% or less.
[0031] [S: 0.01% by mass or less] S is inevitably present as an impurity element, and forms sulfides that deteriorate the bending workability of steel plates and steel plate members. Therefore, the S content must be 0.01 mass% or less. The S content is preferably less than 0.007 mass%, more preferably 0.005 mass% or less, and more preferably 0.004 mass% or less. Alternatively, the S content may be 0 mass%. In other words, the S content may be in the range of 0 mass% or more and 0.01 mass% or less.
[0032] [Remainder] The balance is Fe and unavoidable impurities. As unavoidable impurities, the inclusion of trace elements (e.g., As, Sb, Sn, etc.) brought in depending on the conditions of raw materials, materials, manufacturing equipment, etc. is permitted. Note that, as mentioned above, P and S are generally preferable as their contents are lower, so they can also be called unavoidable impurities. However, these elements are specified as above because the present invention can exert its effects by suppressing the contents of these elements to the specified ranges. For this reason, in this specification, the "unavoidable impurities" that make up the balance are a concept that excludes elements whose composition ranges are specified.
[0033] Furthermore, if necessary, one or more elements selected from the following may be added.
[0034] [Mo: more than 0 mass% and 0.5 mass% or less] Mo, like Cr, is an element that is effective in improving the hardenability and temper softening resistance of steel even in small amounts. To obtain such effects, the Mo content is preferably more than 0 mass%, more preferably 0.001 mass% or more, and even more preferably 0.01 mass% or more. However, if the Mo content is excessive, it becomes difficult to soften the steel sheet by annealing, and there is a risk that the cold workability before quenching will decrease. Therefore, the Mo content is preferably 0.5 mass% or less, more preferably 0.3 mass% or less.
[0035] [B: More than 0% by mass and 0.005% by mass or less] B is an effective element for improving hardenability when added in a small amount. To obtain such an effect, the B content is preferably more than 0 mass%, more preferably 0.0005 mass% or more, and even more preferably 0.001 mass% or more. On the other hand, if the B content is excessive, castability may decrease and B-based compounds may be generated, resulting in a decrease in toughness. Therefore, the B content is preferably 0.005 mass% or less, more preferably 0.0045 mass% or less, and even more preferably 0.004 mass% or less.
[0036] [Ni: more than 0 mass% and 0.5 mass% or less] Ni is an element that is effective in improving the hardenability of steel and in improving low-temperature toughness. To obtain such effects, the Ni content is preferably more than 0 mass%, more preferably 0.01 mass% or more, and even more preferably 0.05 mass% or more. On the other hand, Ni is expensive as an alloy element of steel, and an excessive Ni content leads to an increase in costs in manufacturing steel plate. Therefore, the Ni content is preferably 0.5 mass% or less, more preferably 0.3 mass% or less, and even more preferably 0.15 mass% or less.
[0037] [V: More than 0% by mass and 0.35% by mass or less] V, like Nb, forms carbonitrides in steel and is an effective element for preventing the grains of steel from becoming coarse and for improving the toughness of steel plate members. To obtain such effects, the V content is preferably more than 0 mass%, more preferably 0.001 mass% or more, even more preferably 0.01 mass% or more, and even more preferably 0.05 mass% or more. On the other hand, when the V content exceeds a certain amount, the effect of V becomes saturated. Therefore, the V content is preferably 0.35 mass% or less, more preferably 0.2 mass% or less.
[0038] 2. Microstructure of Steel Sheet The microstructure of the high carbon steel sheet in this embodiment is composed of ferrite and cementite (carbide). The area ratio of each of ferrite and cementite in the microstructure is not particularly limited, and the microstructure may contain a small amount of pearlite, bainite, martensite, etc., as long as the effect of the present invention is not impaired. Specifically, the microstructure of the high carbon steel sheet in this embodiment is a structure in which cementite grains are dispersed in the ferrite matrix. Note that NbC is fine, and therefore is not observed as a carbide even when observed at 2000 times magnification using a scanning electron microscope (SEM).
[0039] In the microstructure of the steel sheet, the spheroidization rate of cementite is preferably 70% or more, more preferably 80% or more, even more preferably 85% or more, and even more preferably 90% or more. The upper limit of the spheroidization rate of cementite is 100%. In this specification, the spheroidization rate of cementite refers to the percentage (%) obtained by dividing the number of cementite grains in a specified observation area having a major axis / minor axis ratio (aspect ratio) of 3 or less by the total number of cementite grains observed in the specified observation area.
[0040] By increasing the spheroidization rate of cementite, the formability of the steel sheet can be improved, the risk of cracks occurring during forming can be prevented, and the finish of cold rolling can be improved.
[0041] Furthermore, in the microstructure of the steel sheet, 2 The number of cementite grains per 1000 μm is preferably 200 or more, more preferably 400 or more, and further preferably 600 or more. 2 By making the number of cementite grains per unit area 200 or more, it is possible to suppress the size of each cementite grain from becoming coarse and remaining as undissolved carbide when heated at high temperatures, and to prevent the remaining undissolved carbide in the steel plate member from becoming the starting point of cracks.
[0042] In addition, the long diameter / short diameter and 1000 μm diameter of cementite in the microstructure of high carbon steel sheet 2 The number of cementite grains per unit area can be measured by image analysis using a scanning electron microscope, as will be described in detail in the Examples.
[0043] 3. Steel Sheet Manufacturing Method The method for producing the high carbon steel sheet in this embodiment can be any known method as long as it can produce a high carbon steel sheet having the above-mentioned composition and a microstructure consisting of ferrite and cementite. An example of the production method will be described below.
[0044] First, a steel material (slab) for rolling having the above-mentioned composition is prepared. The slab can be prepared by any known method. For example, the method for preparing the slab includes a method in which a steel having the above-mentioned composition is melted and a slab is prepared by ingot casting or continuous casting. If necessary, the cast material obtained by ingot casting or continuous casting may be subjected to blooming to obtain a slab.
[0045] Next, the obtained slab is hot-rolled to obtain a hot-rolled steel sheet. The hot-rolling may be performed by any known method under any conditions. For example, the hot-rolling may be performed by setting the heating temperature before the hot-rolling to 1150°C or more and 1300°C or less, and setting the finish rolling temperature to 800°C or more. After the finish rolling, the steel sheet may be coiled at, for example, more than 550°C and 650°C or less.
[0046] After hot rolling, the steel sheet is pickled by any known method to remove scale from the surface layer of the steel sheet.
[0047] The resulting steel sheet is then subjected to annealing, particularly spheroidizing annealing. The annealing process results in almost no pearlite remaining in the microstructure of the resulting annealed steel sheet, and only ferrite remains. A structure in which cementite grains are dispersed in the matrix. Annealing (spheroidizing annealing) usually includes a step of heating the steel sheet, a step of soaking the heated steel sheet, and a step of cooling the steel sheet after soaking.
[0048] The heating rate in the step of heating the steel sheet is not particularly limited, but is preferably 20° C. / h to 250° C. / h. By setting the heating temperature in the range of 20° C. / h to 250° C. / h, it is possible to prevent temperature deviation in the coil during annealing and the resulting variation in hardness of the steel sheet, and also to suppress a decrease in productivity due to a too slow heating rate.
[0049] The soaking temperature in the step of soaking the heated steel sheet is not particularly limited, but is preferably 660° C. or higher and 740° C. or lower. Furthermore, the soaking time in the step of soaking the heated steel sheet is not particularly limited, but is preferably 5 hours or higher and 40 hours or lower. By soaking the steel sheet at 660° C. or higher and 740° C. or lower and 5 hours or higher and 40 hours or lower, the cementite in the steel sheet can be sufficiently spheroidized, and a decrease in productivity of the steel sheet due to excessive heating can be prevented.
[0050] The step of cooling the steel sheet after soaking is not particularly limited, but for example, the steel sheet may be gradually cooled to a predetermined temperature by furnace cooling, followed by rapid cooling. The cooling rate during slow cooling is not particularly limited, but is preferably 1°C / h to 10°C / h. Slow cooling is performed, for example, until the temperature reaches 550°C to 650°C. The cooling rate during rapid cooling is not particularly limited, but is preferably 10°C / h to 300°C / h. After rapid cooling, the temperature is, for example, 50°C or less.
[0051] When such annealing is performed, the type of annealing furnace and the atmosphere composition are not limited, but for example, it can be performed in a batch annealing furnace under an atmosphere of hydrogen, nitrogen, or a mixture thereof. In addition, if necessary, cold rolling may be performed after annealing. In this case, the cold rolling reduction rate can be, for example, in the range of 20% to 70%. Furthermore, if necessary, further annealing, particularly spheroidizing annealing, may be performed after cold rolling.
[0052] The high carbon steel plate in this embodiment manufactured in this manner is punched out to a required size, and after forming, is subjected to heat treatment such as quenching and tempering to manufacture a steel plate member. In this case, even if the heating temperature before quenching is increased, for example, to a temperature exceeding 850°C, particularly to a temperature of 900°C or higher, a steel plate member having a stable balance between hardness and toughness can be manufactured. Therefore, the high carbon steel plate in this embodiment can be suitably used as a processing material for steel plate members that require not only hardness but also good toughness, such as various blades such as circular saws, band saws, and carters, springs, springs, and tools. EXAMPLES
[0053] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to these examples in any way.
[0054] <Example 1> In this Example 1, an experimental steel plate was manufactured by simulating an actual steel plate manufacturing process, and a heat-treated test piece was prepared from the experimental steel plate. The hardness and toughness of the heat-treated test piece were measured, and the balance between them was determined.
[0055] [Manufacturing of experimental steel plates] Steel materials (steel types A to G) having the composition shown in Table 1 below were melted, and the resulting ingots were hot-rolled to a thickness of 30 mm. The hot-rolled 30 mm rough bar was then heated at 1250°C for 30 minutes, and then hot-rolled at a finishing temperature of 920°C to a thickness of 3.0 mm. After rolling, the resulting hot-rolled steel sheet was water-cooled to 650°C at 30°C / s, then inserted into a holding furnace at 620°C, and held there for 30 minutes for furnace cooling. This process imitates coiling and subsequent cooling. After cooling, the resulting hot-rolled steel sheet was further cooled to room temperature, and then pickled to remove surface scale.
[0056] The hot-rolled steel sheet thus obtained was then subjected to a first annealing, cold rolling, and a second annealing in that order. In the first annealing, the steel sheet was heated to 715°C in 5 hours, soaked at 715°C for 10 hours, slowly cooled to 675°C in 12 hours, and further cooled to 200°C or less in 1 hour. Next, the steel sheet after the first annealing was cold rolled from a thickness of 3.0 mm to a thickness of 1.5 mm. In other words, the cold rolling rate was 50%. Finally, the steel sheet after the cold rolling was subjected to a second annealing under the same temperature and time conditions as the first annealing to obtain an experimental steel sheet.
[0057] [Measurement and evaluation of properties of test pieces after heat treatment of experimental steel plate] From the obtained experimental steel plates, heat-treated test pieces were prepared by the method described below, and the hardness and toughness of the heat-treated test pieces were measured to determine the balance between them.
[0058] (Preparation of test pieces after heat treatment) The surface of the experimental steel plate had uneven defects such as indentations and scale marks from hot rolling and cold rolling, so both sides of the steel plate were ground from a thickness of 1.5 mm to a thickness of 1.0 mm to remove the effects of these defects. The experimental steel plate was then cut to an appropriate size required for the characteristic measurements described below to obtain test pieces, which were heated in a salt bath at 910°C for 3 minutes, water-cooled and quenched, and then tempered at 350°C for 10 minutes to obtain heat-treated test pieces. The tempering temperature of 350°C was set so that the Vickers hardness of the heat-treated test pieces was about 560HV.
[0059] (Hardness) The hardness of the heat-treated test pieces was measured by Vickers hardness. The Vickers hardness was measured at 5 points at 1 / 4 of the thickness of the heat-treated test pieces using a Vickers hardness tester in accordance with the JIS Z 2244:2009 standard with a test load of 5 kgf, and the average value was calculated. The results are shown in Table 2 below, together with the heating conditions before quenching and the tempering conditions.
[0060] (Toughness) The toughness of the heat-treated test specimen was measured based on the VDA bending test. The size of the heat-treated test specimen was 1.0 mm thick x 16 mm wide (perpendicular to the rolling direction) x 60 mm long. The cut end faces of the heat-treated test specimen were finished by milling. Specifically, the VDA bending test was evaluated under the following measurement conditions based on the VDA standard (VDA238-100) specified by the German Association of the Automotive Industry. In this example, the displacement at the maximum load obtained in the bending test was converted to an angle based on the VDA standard, and the bending angle was calculated. The results are shown in Table 2 below together with the heating conditions before quenching and the tempering conditions. Measurement conditions Test method: Roll support, punch press Roll diameter: φ30mm Punch shape: Tip R = 0.4 mm Distance between rolls: Sheet thickness x 2 + 0.5 mm Push-in speed: 20mm / min Test piece dimensions: 16mm x 60mm Bend ridge: perpendicular to rolling direction Testing machine: Shimadzu Corporation universal material testing machine Autograph AG-X plus
[0061] (Balance of hardness and toughness) Regarding the measured Vickers hardness and the calculated VDA bend angle, the tempering temperature was set so that the Vickers hardness was about 560HV, so the balance between hardness and toughness was judged mainly based on whether the VDA bend angle had a good value. In this Example 1, the balance between hardness and toughness was judged as follows: ◯ (good) when the VDA bend angle was 35° or more, △ (slightly poor) when it was 30° or more and less than 35°, and × (poor) when it was less than 30°. The judgment results are also summarized in Table 2 below, together with the heating conditions before quenching and the tempering conditions.
[0062] In the composition of the components shown in Table 1 below, "-" means that no addition was made, and "<" means that the element was below the lower analytical limit.
[0063] [Table 1]
[0064] [Table 2]
[0065] [Consideration] As shown in the above Table 2, the judgment results of Test Specimen No. 1 and Test Specimen No. 6, whose steel composition satisfied the conditions of the present invention, were "Good." In other words, it was found that even if the heating temperature before quenching was 910°C, the toughness after quenching and tempering did not decrease, and a good balance between hardness and toughness was obtained.
[0066] In contrast to this, test piece No. 2, which did not contain Nb but contained Ti in the composition of the steel type, was judged as "x", and the toughness after quenching and tempering was significantly reduced.
[0067] Test piece No. 3, which did not contain Nb in the composition of the steel, was judged as "△", and the toughness after quenching and tempering was slightly decreased.
[0068] Test piece No. 4, which did not contain Nb and contained a large amount of Si in the composition of the steel type, was judged as "X", and the toughness after quenching and tempering was significantly reduced.
[0069] Test piece No. 5, which did not contain Nb and contained a large amount of Mo in the composition of the steel, was judged as "x", and the toughness after quenching and tempering was significantly reduced.
[0070] The steel composition contained Nb, but the test piece No. 7, which contained a large amount of Ti, was judged as "x", and the toughness after quenching and tempering was significantly reduced.
[0071] <Example 2> In this Example 2, a steel plate was manufactured using a manufacturing machine that is actually used for manufacturing steel plate, the microstructural parameters and properties of the steel plate were measured, a heat-treated test piece was prepared from the steel plate, and the hardness and toughness of the heat-treated test piece were measured to determine the balance between them.
[0072] [Steel plate manufacturing] Steel materials (steel types H and I) having the composition shown in Table 3 below were melted, and then slabs were produced by continuous casting. The obtained slabs were heated and then rough rolled to make rough bars with a thickness of 30 mm. The rough rolling end temperature was about 1070°C. Next, the finish rolling end temperature was set to 890°C, and the steel was finish rolled to a thickness of 1.6 mm, and coiled at 610°C. Next, the obtained hot-rolled steel sheets were cooled to room temperature and pickled to remove scale.
[0073] The hot-rolled steel sheets were then annealed and cold-rolled. In the annealing, the steel sheets were heated to 690°C in about 20 hours, soaked at 690°C for 26 hours, and then cooled to 60°C or less in about 34 hours. Finally, the annealed steel sheets were cold-rolled from a thickness of 1.6 mm to a thickness of 0.6 mm. In other words, the cold rolling rate was 63%.
[0074] [Measurement of microstructural parameters and properties in steel sheets] The microstructural parameters and properties of the obtained steel sheets were measured by the methods described below.
[0075] (Measurement of Microstructural Parameters) The steel plate obtained by the above method was cut to an appropriate size to obtain a test piece of the steel plate. The surface of the thickness cross section of the test piece parallel to the rolling direction at the center of the plate width direction was polished, and then etched with picral solution. The microstructure at 1 / 4 of the plate thickness was observed with a scanning electron microscope at a magnification of 2000 times. The observation field was 1000 μm. 2 It was decided.
[0076] The microstructure observed was a structure in which white cementite grains were dispersed in the ferrite matrix. The NbC was fine and was not observed as carbide at 2000x magnification. Image analysis revealed that the NbC was not observed as carbide at 2000x magnification. 2 The number of white cementite grains was counted. 2 The long and short diameters of each cementite grain were measured by image analysis. The number of cementite grains with a long / short diameter ratio (aspect ratio) of 3 or less was counted. 2 The spheroidization rate (%) was calculated by dividing the number of cementite grains per unit area by the number of cementite grains per unit area. The results are shown in Table 4 below.
[0077] (Hardness) The Rockwell hardness (HRB) of the steel sheets obtained by the above method was measured in accordance with the Rockwell hardness test specified in JIS G 2245: 2016. The results are summarized in Table 4 below. The results are summarized in Table 4 below.
[0078] (Tensile properties) From the steel plate obtained by the above method, JIS No. 5 test pieces were prepared in the direction perpendicular to the rolling direction. Using the test pieces, the yield point (YP: Yield Point) (unit: MPa), ultimate strength (TS: Tensile Strength) (unit: MPa), and elongation (EL: Elongation) (unit: %) were obtained in accordance with the tensile test method for metallic materials of JIS Z 2241:2011. The results are summarized in Table 4 below.
[0079] [Measurement and evaluation of properties of test pieces after heat treatment of steel plate] From the obtained steel plates, heat-treated test pieces were prepared by the method described below, and the hardness and toughness of the heat-treated test pieces were measured to determine the balance between them.
[0080] (Preparation of test pieces after heat treatment) The steel plate was cut into a suitable size required for the characteristic evaluation described below to obtain a test piece, which was heated in a salt bath at 910°C for 3 or 10 minutes, water-cooled and quenched, and then tempered at 350°C or 325°C for 10 minutes to obtain a heat-treated test piece. The tempering temperature of 350°C was set so that the Vickers hardness of the heat-treated test piece was about 560HV. On the other hand, the tempering temperature of 325°C was set so that the Vickers hardness of the heat-treated test piece was about 600HV.
[0081] (Hardness and toughness) Regarding the hardness and toughness of the heat-treated test pieces, although the plate thickness of the test pieces was different, the Vickers hardness and VDA bending angle were measured by the same measuring method and under the same measuring conditions as in the above-mentioned Example 1. The results are summarized in Table 5 below, together with the heating conditions before quenching and the tempering conditions.
[0082] (Balance of hardness and toughness) Regarding the measured Vickers hardness and the calculated VDA bending angle, the tempering temperature was set so that the Vickers hardness was about 560HV or about 600HV, so the balance between hardness and toughness was judged mainly based on whether the VDA bending angle had a good value. If the Vickers hardness value is set large, the VDA bending angle value becomes small. Therefore, in this Example 2, for test piece No. 8 to test piece No. 11, the balance between hardness and toughness was judged as ◯ (good) when the VDA bending angle was 40° or more, and × (bad) when it was less than 40°. On the other hand, for test piece No. 12 to test piece No. 15, the balance between hardness and toughness was judged as ◯ (good) when the VDA bending angle was 30° or more, and × (bad) when it was less than 30°. The judgment results are also summarized in Table 5 below, together with the heating conditions before quenching and the tempering conditions.
[0083] In the component compositions shown in Table 3 below, "-" indicates that no additive was added.
[0084] [Table 3]
[0085] [Table 4]
[0086] [Table 5]
[0087] [Consideration] As shown in the above Table 5, the test specimens No. 8 and No. 9, whose steel composition satisfied the conditions of the present invention, were judged as "good" regardless of the heating time. In other words, it was found that even if the heating temperature before quenching was high and the heating time before quenching was varied, the toughness after quenching and tempering did not decrease, and a good balance between hardness and toughness was stably maintained.
[0088] In contrast, for test specimen No. 10 and test specimen No. 11, which do not contain Nb in the composition of the steel, test specimen No. 10, which had a heating time of 3 minutes, was judged to be "Good," but test specimen No. 11, which had a heating time of 10 minutes, was judged to be "Poor." In other words, when the heating temperature before quenching was high, the toughness after quenching and tempering was significantly reduced due to fluctuations in the heating time before quenching.
[0089] In addition, when the Vickers hardness was set to about 600 HV, the test pieces No. 12 and No. 13, whose steel composition satisfied the conditions of the present invention, were both judged as "good." In other words, it was found that even when the Vickers hardness was set to a different value, the toughness after quenching and tempering did not decrease, and a good balance between hardness and toughness was stably maintained.
[0090] In contrast, the test pieces No. 14 and No. 15, which do not contain Nb in the composition of the steel, were both judged as "X." In other words, when the heating temperature before quenching was high, the toughness after quenching and tempering was significantly reduced, and further, the toughness after quenching and tempering was also significantly reduced by fluctuations in the heating time before quenching.
[0091] <Example 3> In this Example 3, similarly to Example 2, a steel plate was manufactured using a manufacturing machine that is actually used for manufacturing steel plate, and a heat-treated test specimen was prepared from the steel plate. The hardness and toughness of the heat-treated test specimen were measured, and the balance between them was determined.
[0092] [Steel plate manufacturing] After the steel material having the composition of steel type H shown in Table 3 above was melted, a slab was produced by continuous casting. The obtained slab was heated and then rough rolled to a rough bar having a thickness of 35 mm. The end temperature of the rough rolling was about 1090°C. Next, the end temperature of the finish rolling was set to 890°C, and the steel was finish rolled to a thickness of 2.0 mm, and coiled at 610°C. Next, the obtained hot-rolled steel sheet was cooled to room temperature and pickled to remove scale.
[0093] The obtained hot-rolled steel sheet was then annealed. In the annealing, the steel sheet was heated to 690°C in about 20 hours, soaked at 690°C for 26 hours, and then cooled to 60°C or lower in about 34 hours. That is, in this Example 3, the steel sheet was manufactured by a process in which the cold rolling process was omitted from the manufacturing process of the steel sheet in the above-mentioned Example 2.
[0094] [Measurement and evaluation of properties of test pieces after heat treatment of steel plate] From the obtained steel plates, heat-treated test pieces were prepared by the method described below, and the hardness and toughness of the heat-treated test pieces were measured to determine the balance between them.
[0095] (Preparation of test pieces after heat treatment) The steel plate was cut to an appropriate size required for the characteristic evaluation described below to obtain a test piece, which was then heated in a salt bath at 910°C for 10 minutes, water-cooled and quenched, and then tempered at 450°C, 425°C or 400°C for 10 minutes to obtain a heat-treated test piece. The tempering temperatures of 450°C, 425°C and 400°C were set so that the Vickers hardness of the heat-treated test piece was about 470HV to 520HV.
[0096] (Hardness and toughness) Regarding the hardness and toughness of the heat-treated test pieces, although the plate thickness of the test pieces differed, the Vickers hardness and VDA bending angle were measured using the same measuring method and under the same measuring conditions as in the above-mentioned Examples 1 and 2. The results are summarized in Table 6 below, together with the heating conditions before quenching and the tempering conditions.
[0097] (Balance of hardness and toughness) Regarding the measured Vickers hardness and the calculated VDA bending angle, the tempering temperature was set so that the Vickers hardness was about 470HV to 520HV, so the balance between hardness and toughness was judged mainly based on whether the VDA bending angle had a good value. In general, the thicker the steel plate (heat-treated test piece), the larger the strain on the outside of the bent part, so the absolute value of the VDA bending angle becomes smaller. That is, since the thickness of the heat-treated test piece in this Example 3 is 2.0 mm, it is expected that the absolute value of the VDA bending angle will be smaller than the heat-treated test piece in the above-mentioned Example 1 having a thickness of 1.0 mm and the heat-treated test piece in the above-mentioned Example 2 having a thickness of 0.6 mm. On the other hand, if the Vickers hardness value is set small, the value of the VDA bending angle will be large. Therefore, in this Example 3, the balance between hardness and toughness was judged comprehensively in consideration of these factors. For test piece No. 16, the balance was judged to be good if the VDA bend angle was 29° or more. For test piece No. 17, the balance was judged to be good if the VDA bend angle was 25° or more. For test piece No. 18, the balance was judged to be good if the VDA bend angle was 23° or more. The judgment results are also shown in Table 6 below, together with the heating conditions before quenching and the tempering conditions.
[0098] [Table 6]
[0099] [Consideration] As shown in Table 6 above, the results of the evaluation of the balance between hardness and toughness of test specimen No. 16 to test specimen No. 18, whose composition of the steel grade satisfies the conditions of the present invention, were "good". That is, even if the heating temperature before quenching is high and the plate thickness is 2.0 mm, the toughness after quenching and tempering does not decrease significantly, and the test specimens have a good balance between hardness and toughness. In addition, in test specimen No. 16 to test specimen No. 18, the tempering temperature is changed, and the Vickers hardness is changed to a certain extent accordingly. However, it was found that the toughness of the test specimens after quenching and tempering does not change significantly, and each test specimen maintains a certain good bendability. On the other hand, according to the results of test specimen No. 11 and test specimen No. 15 in Table 5 in the above-mentioned Example 2, it is found that even if the plate thickness is 0.6 mm, which is thinner than the test specimen of this Example 3, when the composition of the steel grade does not contain Nb, the toughness after quenching and tempering is significantly decreased when the heating temperature before quenching is increased and the tempering temperature is changed.
[0100] In this way, the high carbon steel plate of the present invention can stably maintain a good balance between hardness and toughness even if the steel plate is thick. Therefore, even if the steel plate is processed into, for example, a spring, it is expected that the steel plate will not easily break due to brittleness, and the high carbon steel plate of the present invention can be suitably processed into steel plate members for many tools and the like.
Claims
1. C: 0.75% by mass or more and 1.10% by mass or less, Si: 0.05% by mass or more and 0.40% by mass or less, Mn: 0.05% by mass or more and 0.70% by mass or less, Cr: 0.35% by mass or less, Nb: 0.005% by mass or more and less than 0.020% by mass, Ti: 0.02% by mass or less, Al: 0.001% by mass or more and 0.050% by mass or less, P: 0.03% by mass or less, and S: 0.01% by mass or less and the balance being Fe and unavoidable impurities, The microstructure of the steel plate is a high carbon steel plate having a structure in which cementite grains are dispersed in a ferrite matrix.
2. The high carbon steel plate according to claim 1, wherein the spheroidization rate of the cementite is 70% or more.
Citation Information
Patent Citations
Steel material for cutlery excellent in wear resistance and toughness
JP2009161809A
High carbon steel sheet and manufacturing method therefor
JP2017179596A